Transfobia en Twitter. El caso Rachel Levine al comienzo de la presidencia de Joe Biden - Dra. Paula REQUEIJO REY,Dra. Graciela PADILLA CASTILLO,Dra. Paula DÍAZ ALTOZANO (Fonseca, Journal of Communication, 2023)
On 19 January 2021, US President Joe Biden nominated Dr Rachel Levine to be Under Secretary of Health. She is the first trans person to hold federal office. Transphobia surfaced on Twitter, where numerous users mocked Levine, attacked her for her appearance and insisted she was a man. The aim of this paper is to understand, quantitatively and qualitatively, the repercussions of the appointment. We researched the hashtags with which transphobic tweets were tagged, determined when they began to be posted, when they peaked and when they declined, and identified the most popular users, using the Hashtagify.me application